Inside Cover: Phenotypic Discovery of Neuroprotective Agents by Regulation of Tau Proteostasis via Stress‐Responsive Activation of PERK Signaling (Angew. Chem. Int. Ed. 4/2021). Issue 4 (4th January 2021) - Shin, Young‐Hee; Cho, Hana; Choi, Bo Young; Kim, Jonghoon; Ha, Jaeyoung; Suh, Sang Won; Park, Seung Bum
Abstract : Neurodegenerative diseases are characterized by the accumulation of misfolded proteins such as tau protein. In their Research Article on page 1831, Seung Bum Park and co‐workers perform a cell‐based phenotypic screening and identify a small molecule, SB1617, capable of suppressing abnormal assembly of tau protein under ER stress. The label‐free target identification and mode of action studies revealed that SB1617 treatment leads to the restoration of proteostasis in a stress‐responsive manner.